FTA and PIM research informs the renewal of community forest concessions in the Maya Biosphere Reserve (Guatemala) - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
Scientific evidence generated by PIM/FTA informed technical documents of the National Council for Protected Areas and guided the evaluation process of community forest concessions, which are up for renewal, and associated deliberation. PIM and FTA generated evidence that communities can capably manage and conserve forest. This, together with strong social mobilization, resulted in the revision of the norms for granting concessions in the multiple use zone of the reserve and, based on it, the first renewal of a community concession contract (Cooperative Carmelita) in December. Contract renewal is expected to continue in 2020.